A half century of permanent plot observation in Budongo Forest, Uganda: histories, highlights and hypotheses - Sheil, Douglas (MAB UNESCO, 1998)
W.J. Eggeling established several 1.86 ha permanent sample plots (PSPs) in Budongo Forest, Uganda, during the 1930s and 1940s. Using data from these plots he described Budongo's vegetation within a comprehensive ‘successional’ framework. Some of these plots have been re-measured on several occasions since their establishment. Five plots were fully reassessed in 1992-1993 (c. 9 ha total including c. 5,000 stems ³ 10 cm dbh). This paper outlines the history of the unique Budongo evaluations and highlights the significance and opportunities available from long term PSP studies. Eggeling’s (1947a) framework remains a classic example of succession in which species numbers decline in later stages. Disturbance models for local diversity maintenance have been implied and Connell (1978) chose to use Eggeling’s account of Budongo as the main illustration of his intermediate disturbance hypothesis. Community change at Budongo can now be directly evaluated using the long term PSP data. Those plots which have been disturbed do indeed show an increase in species numbers. More surprisingly however the undisturbed late successional forest has not shown the expected decrease in species richness. The implications of the various observations are examined and the theoretical context is considered. It is suggested that the intermediate disturbance model is limited, and that a more comprehensive theory would include the many influences that effect regeneration within a changing environment. Any influences or processes which allows the successful regeneration of species within communities where they are not already present has the ability to increase local species richness. In long lived tree communities such species augmentation may be brought about by many types of environmental changes, both sudden (as in disturbance) and also by gradual and progressive influences.